The βc receptor family – Structural insights and their functional implications. Issue 2 (August 2015) - Broughton, Sophie E.; Nero, Tracy L.; Dhagat, Urmi; Kan, Winnie L.; Hercus, Timothy R.; Tvorogov, Denis; Lopez, Angel F.; Parker, Michael W.
Highlights GM-CSF and IL-3 are pleiotropic cytokines with roles in health and disease. New crystal structure of IL3Rα reveals novel open and closed conformations. Membrane proximal and transmembrane domain movement likely to initiate signaling.